2016
DOI: 10.1039/c6ra17771a
|View full text |Cite
|
Sign up to set email alerts
|

Carbon nanotube-induced migration of silver nanowire networks into plastic substrates via Joule heating for high stability

Abstract: The hydrothermal and mechanical stability of transparent conducting films is a prerequisite for commercial applications in optoelectronic devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…A high achieved temperature could enlarge the applicable areas of the heater. The Ag heaters can achieve higher temperature and faster response and recovery time under relatively low applied voltages and have better performance than those based on AgNWs, PEDOT:PSS, graphene, and CNTs. ,,, Figure c,d show fron-side and back-side heating result images of FLIR with a 128 Ω resistor under 18 V applied voltage. It can be found that although a lower temperature is achieved at the back-side surface, the temperature distribution seems more uniform than that of the front-side surface.…”
Section: Resultsmentioning
confidence: 99%
“…A high achieved temperature could enlarge the applicable areas of the heater. The Ag heaters can achieve higher temperature and faster response and recovery time under relatively low applied voltages and have better performance than those based on AgNWs, PEDOT:PSS, graphene, and CNTs. ,,, Figure c,d show fron-side and back-side heating result images of FLIR with a 128 Ω resistor under 18 V applied voltage. It can be found that although a lower temperature is achieved at the back-side surface, the temperature distribution seems more uniform than that of the front-side surface.…”
Section: Resultsmentioning
confidence: 99%
“…The thermal process can be incompatible with many sensitive materials such as plastic substrates. Various additives to Ag NWs have been shown to effectively improve upon some of these shortcomings, including carbon nanotube and graphene, , precursors for the sol–gel synthesis of metal oxides, , conducting and insulating polymers, and physical-vapor-deposited metal oxides; however, compromises such as increased process complexity and deviations from Ag NWs’ optimal properties often accompany improvements, and a comprehensive solution has not been attainable. Consequently, a method that can simultaneously provide the functions of passivation, protection, surface homogeneity, gas-permeation barrier, and junction-fusing to the Ag NWs film while retaining its flexibility and processability will provide a major breakthrough to the development of the Ag NWs TCF technologies.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from their low sheet resistance, ≈10 Ω sq −1 , metallic nanowire‐based networks must be very long to minimize junction resistance and they should also be defect free to reach conductivity as close as the corresponding bulk value. Several groups have reported transparent thin‐film heaters based on metallic nanowires, ITO, CNTs and polymer film with composite materials, e.g., with Ag nanowires, etc. Most of these thin‐film heaters are very sensitive to deformation and the applied voltage renders them extremely unsuitable for demanding situations.…”
Section: Introductionmentioning
confidence: 99%